An empirical study of dictionary use in version. - Mackintosh, Kristen. (University of Ottawa (Canada), 1995)
This thesis reports on an empirical study of dictionary use in translation from a foreign into a native language (version). The purpose of the study was to gather information on how student translators use dictionaries in version, particularly when translating specialized texts, and to see what effects certain aspects of dictionaries have on them. The study consists of two tests conducted on translation students (Francophone and Anglophone) at the University of Ottawa. The first test was designed to gather general information about students' use of dictionaries in version. The main issues explored in this test are the following: (1) Integration of dictionary use into the version task; (2) Most common reasons for consulting dictionaries; (3) Types of dictionaries most frequently consulted; (4) Elements of entries most frequently used; (5) Most common and most satisfactory dictionary-use strategies; (6) Major causes of dissatisfaction; (7) Choice of definitional metalanguage. The second test was designed to further explore some of the findings of test 1 on the issue of definitional metalanguage. Specifically, it was conceived to measure the ability of translation students to cope with L1 and L2 definitional metalanguage.
Keywords: Language, Linguistics.